Performance Evaluation of Semi-Active Cab Vibration Isolation of a Wheel Loader Using Fractional-Order PID Controller - Chi-Huan Canh; Van-Cuong Bui; Van-Quynh Le (Journal of Fuzzy Systems and Control, 2026)
Cab vibration in wheel loaders significantly affects operator ride comfort and working performance. Therefore, this paper presents an approach to improving the vibration isolation performance of the cab in a wheel loader system. First, a three-degree-of-freedom dynamic model is established to characterize the vibration behavior. Subsequently, a semi-active cab vibration isolation (SCVI) system is proposed. To generate the semi-active control force, a fractional-order PID (FOPID) controller is developed. Additionally, a conventional PID controller is considered to facilitate a rigorous and comprehensive evaluation of the proposed control strategy. The grey wolf optimization (GWO) algorithm is employed to tune the controller parameters optimally. Finally, the performance of the proposed system is validated through simulations conducted in the MATLAB/Simulink environment. The results indicate that the proposed SCVI system based on FOPID controller reduces the root mean square (RMS) values of seat acceleration (azs), cab acceleration (azc), and cab vibration isolation mount deflection (zcf) by 20.76%, 22.33%, and 48.09%, respectively, compared to the passive cab vibration isolation (PCVI) system, demonstrating a significant improvement in operator ride comfort. These findings contribute to the advancement of cab vibration isolation systems for construction machinery.